ISLAMIC ETHICS AND ENVIRONMENTAL STEWARDSHIP: A SYSTEMATIC LITERATURE REVIEW OF QURANIC TEACHINGS AND MODERN APPLICATIONS - Cholid Fadil (Penelitian dan Pengembangan Ilmu, 2024)
This research explores the influence of the teachings of the Qur'an on contemporary environmental practices among Muslim communities, with a focus on the relevance of environmental ethics in the current global context. The aim of this research is to identify the teachings of the Qur'an related to environmental management and analyze their application in various cultural contexts. The research method used is a systematic literature review, with thematic analysis of relevant studies. The research results show that the teachings of the Qur'an provide a strong ethical foundation for sustainability practices, although there are challenges in implementing them in various cultures. The implications of this research emphasize the need to integrate Islamic values ​​in environmental policies and daily practices, as well as encourage collaboration between government, educational institutions and civil society to increase awareness of environmental responsibility.